Morphological Diversity of Fruits, Seeds and Seedlings of Pongamia (Pongamia pinnata (L.) Pierre) in Java Island - NFN Supriyanto; Iskandar Z. Siregar; Ani Suryani; Aam Aminah; Dede J. Sudrajat (Jurnal Perbenihan Tanaman Hutan, 2017)
Pongamia (Pongamia pinnata (L.) Pierre) is one of a potential tree species to produce biodiesel. Pongamia-based biodiesel development program is still constrained by the availability of quality and quantity seeds due to the limited of seed sources. The purpose of this research was to identify the morphological diversity of fruits, seeds and seedlings from 5 populations in Java Island. Randomized completely design and randomized block design were used to assess the difference of fruits, seeds and seedlings morphological characteristics among populations. Principal component and hierarchy cluster analysis were used to explain variation pattern among populations. The results showed that the difference of populations was significantly affected by the difference of fruits, seeds, and seedlings morphology of pongamia. Seeds from Carita population showed good quality seed indicators with moisture content of 19.31%, and germination capacity of 74.50%. Sturdiness quotient of the seedling was 10.78. Contribution of genetic factor was higher than environtment factor is relation to the differences of morphological characteristics of fruits, seeds and seedlings of pongamia. Morphological character of the five populations can be divided into 3 groups, i.e. the first group of Batukaras and Kebumen, second group of Alas Purwo and Baluran, and group 3 was Carita.